Maritime Academy Graduates 31 Cadets Here Today - Vallejo Times-Herald (Vallejo Times-Herald)
In impressive ceremonies, scheduled to start at 10 a..m., 31 young men, inluding four from Vallejo, will graduate from the California Maritime Academy today. Degrees, licenses, and commissions will be given the graduates to conclude their three years of study, and active, practical sea-going training and education. The annual commencement exercises will be attended by a galaxy of Navy officials, U.S. Maritime officials and notables in private shipping industry, and will be held in Mayo Hall at the academy.